Cutaneous Manifestations in Pediatricpatients with chronic Liver Disease - Ghada Farghaly Abd-Alalim Mahmoud; Sherif Ramzy El-Baroudy (2022)
(3GdCYQGV GdLdOjI dOi GdCWaGd GdPjf jYGfhf ef CeQGV GdcHO GdeRefg NGUI aj GdHdOGf GdefNaVI hGdeJhSWI GdONd(B. (3hGdgOa ef gPG GdYed gh Jbjje MOhK GdCeQGV GdLdOjI dOi gDdGA GdCWaGd(B. (3hbO GTJedJ GdOQGSg Ydi eGFg Wad jJQGhM CYeGQge ef 6 TghQ hMJi 12 Sfg GdeJQOOjf Ydi YjGOI CeQGV GdcHO HeSJTai CWaGd LGeYg GdbGgQg aj GdaJQg ef CZSWS 2018 hMJi aHQGjQ 2019(B. (3hbO Je CNP GdJGQjN GdeQVj dLejY GdMGdGJ hGdaMU GdEcdjfjcj hGdPj GTJed Ydi OQGSI CYQGV GdcHO GdeRefg hGdCYQGV GdLdOjI GdeUGMHg dg hGdaMhUGJ GdeYedjI GddGReI dPdc hbO Je JbSjege Edi eLehYJjf dJSgjd GdOQGSI(B.s
Thesis (M.Sc.)-Cairo University,2022.
Bibliography: p. 85-99.
Keywords: Pediatrics; Skin manifestations